Climate change over the extratropical southern hemisphere: the tale from an ensemble of reanalysis datasets - Solman, Silvina Alicia (2016)
In this study, a set of five reanalysis datasets [ERA-Interim, NCEP–DOE AMIP-II reanalysis (R2), MERRA, the Twentieth Century Reanalysis (20CR), and the CFS Reanalysis (CFSR)] is used to provide a robust estimation of precipitation change in the middle-to-high latitudes of the Southern Hemisphere during the last three decades. Based on several metrics accounting for the eddy activity and moisture availability, an attempt is also made to identify the dynamical mechanisms triggering these changes during extended summer and winter seasons. To that aim, a weighted reanalysis ensemble is built using the inverse of the variance as weighting factors for each variable. Results showed that the weighted reanalysis ensemble reproduced the observed precipitation changes at high and middle latitudes during the two seasons, as depicted by the GPCP dataset. For the extended summer season, precipitation changes were dynamically consistent with changes in the eddy activity, attributed mostly to ozone depletion. For the extended winter season, the eddy activity and moisture availability both contributed to the precipitation changes, with the increased concentration of greenhouse gases being the main driver of the climate change signal. In addition, output from a five-member ensemble of the high-resolution GFDL CM2.5 for the period 1979– 2010 was used in order to explore the capability of the model in reproducing both the observed precipitation change and the underlying dynamical mechanisms. The model was able to capture the rainfall change signal. However, the increased availability of moisture from the lower levels controls the precipitation change during both summer and winter.